Metode Pengeringan Terhadap Proses Produksi Simplisia Akar Murbei (Morus Alba Radix) dan Akar Kuning (Arcangelisia Flava Radix) - Cica Riyani; Nura Purnamasari; Elisabeth Dhiu (Universitas Kadiri, 2022)
The drying of mulberry roots and yellow roots is part of the stages of making simplicia. This drying aims to reduce the water content of the plant roots. The purpose of this study was to determine the effect of natural and artificial drying on simplicia processing mulberry and yellow roots. The method used in this study is an experimental method using a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment was drying in an oven at a temperature of 40oC, 50oC, 60oC and heat from the sun. Each type of plant was tested separately. The results of the mulberry root research: the highest weight loss was in the T60 treatment (36%) and the lowest was in the TM solar heat treatment (31%), the lowest moisture content was in the T50 (2%) and TM (9%) treatment and the lowest ash content was the T40 treatment (2 %) and the highest is TM (3%). The results of the yellow root research: the highest weight loss was in the treatment T60 (51%) and the lowest was TM (24%), the lowest water content was T50 (4%) and the highest was TM (7%), the highest ash content was TM (3.8%) and lowest T50 (2.1 %). Pengeringan akar murbei dan akar kuning adalah bagian dari tahapan pembuatan simplisia. Pengeringan ini bertujuan untuk mengurangi kadar air dari akar tanaman tersebut. Adapun tujuan dari penelitian ini adalah untuk mengetahui pengaruh pengeringan alami dan buatan terhadap pengolahan simplisa akar murbei dan akar kuning. Metode yang digunanakan dalam penelitian ini adalah metode percobaan dengan menggunakan rancangan acak lengkap (RAL) dengan 4 perlakuan dan 3 ulangan. Perlakuan adalah pengeringan dengan oven pada suhu 40oC, 50oC, 60oC dan panas dari matahari. Masing-masing jenis tanaman diuji secara terpisah. Hasil penelitian akar murbei : susut bobot tertinggi pada perlakuan T60 (36%) dan terendah pada perlakuan panas matahari TM (31%), Kadar air terendah perlakuan T50 (2%) dan TM (9%) dan kadar abu terendah perlakuan T40 (2%) dan tertinggi TM (3%). Hasil penelitian akar kuning : susut bobot tertinggi pada perlakuan T60 (51%) dan terendah TM (24%), kadar air terendah T50 (4%) dan tertinggi TM(7%), kadar abu tertinggi TM (3,8%) dan terendah T50 (2,1 %).